ASSESSMENT OF GENETIC DIVERSITY IN RICE (ORYZA SATIVA) GERMPLASM USING SALTOL AND AROMATIC SSR MARKERS - KAREEM, M; SABAR, M; Ali, Q; ABBAS, A; MUBASHAR, U; AHMAD, S; ASHFAQ, M (Biological and Clinical Sciences Research Journal, 2024)
Rice (Oryza sativa) serves as a staple food for nearly half of the global population. Soil salinity has a major effect on plant growth and the production of rice all over the world. The aromatic properties of the rice are another important aspect from a market perspective. The experiment was conducted at Rice Research Institute Kala Shah Kaku. The randomized complete block design with three replications. Molecular markers in genetics are DNA segments linked to a region of the genome. To differentiate one DNA sequence from an unknown DNA pool, molecular markers are used. Most plant genomes include simple sequence repeats (SSRs), which are widely distributed and highly polymorphic sequences. These are often employed in population genetic research, paternity testing, and DNA fingerprinting. Four Salinity resistant linked gene SSR markers (RM-7075, RM-562, RM-152, RM-WN-13903), the results of these markers show that, accession 27141, 17146, 27731, 27745, and 27789 show all the resistant genes, and 27727 shows least resistant gene. Two aromatic SSR markers (Badex and RM-23-120) were used and 27131, 27141, 27146, 27161, 27166, 27202, 27207, 27731, 27745, and 27769 show highly aromatic properties to screen out salt-tolerant and enhanced aromatic accessions and 27141, 27146, 27731, and 27745 have both highly salt resistant and aromatic genes. From this experiment, it is identified that the accessions are significantly high-yielding, and have salinity-resistant genes the accessions show both salt-tolerant genes and have aromatic properties used further in breeding programs and go under the verity development process.